The dynamic problem of the elastic half-plane due to a force at its boundary - Bich, Nguyen Dang (Vietnam Journal of Mechanics, 1986)
In this paper we presents the problem so put with initial condition according to stress a difference from the problem of boundary this problem answer not only the condition of boundary but also the initial condition. The problem gives solution in two eases the initial condition is the root of sadow oaky problem and it is the root of Flam ant problem.